1988
DOI: 10.1093/oxfordjournals.humrep.a136734
|View full text |Cite
|
Sign up to set email alerts
|

Immunological and biological potencies of the different molecular species of gonadotrophins

Abstract: Pituitary gonadotrophins (follicle-stimulating hormone, FSH; luteinizing hormone, LH) exist in different molecular forms within the anterior pituitary gland and serum of several non-mammalian and mammalian species, including man. The number and relative abundance of each gonadotrophin species will depend on the specific technique utilized for their isolation, the tissue source and the physiological status of the donor. Intracellular FSH and LH from glands of rodents (hamsters and rats) and primates exhibit cha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
36
0

Year Published

1994
1994
2016
2016

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 104 publications
(38 citation statements)
references
References 0 publications
2
36
0
Order By: Relevance
“…The polymorphism of follicle-stimulating hormone (FSH) has previously been described in males and females from different species. These studies were mainly based on differences in the isoelectric point determined by the content of sialic acid, the outer terminal sugar of the carbohydrate chain [4, 5, 6, 7]. …”
Section: Introductionmentioning
confidence: 99%
“…The polymorphism of follicle-stimulating hormone (FSH) has previously been described in males and females from different species. These studies were mainly based on differences in the isoelectric point determined by the content of sialic acid, the outer terminal sugar of the carbohydrate chain [4, 5, 6, 7]. …”
Section: Introductionmentioning
confidence: 99%
“…This differential glvcosylation, in turn, exerts a marked influence on circulating half-life, receptor binding affinity, and in vitro and in vivo biological activities [5], It has been shown that carbo hydrates are needed for the full expression of the biologi cal activity [6]. Sialic acid determines the circulating halflife of the hormone [7], as well as the receptor affinity in vitro [5], The results obtained in experimental animals as well as in studies carried out in children, adults, and aging men and women under different physiological conditions have shown that the hormonal status regulates the sialic acid content of FSH isoforms [8,9], In males, differences have been demonstrated in charge distribution by castra tion [10,11], antiandrogen administration [12], during sexual maturation [13,14], and by in vitro testosterone treatment [15]. There is no evidence of the hormonal influence upon the carbohydrate inner structure of pitu itary FSH isohormones and the relationship between this carbohydrate inner structure of FSH isohormones and their bioactivity.…”
Section: Introductionmentioning
confidence: 99%
“…The 92-amino acid ␣-chain and the 111-amino acid ␤-chain have each two Nlinked oligosaccharide chains presented as complex heterogeneous multiantennary structures (3). The variable degree of glycosylation, especially of sialylation, creates a spectrum of FSH isoforms with differences in charge, bioactivities, and elimination halflives (4,5).…”
mentioning
confidence: 99%